Simple prediction of long‐term clinical outcomes in patients with mild hepatitis C recurrence after liver transplantation. (14th June 2016) - Gambato, Martina; Crespo, Gonzalo; Torres, Ferran; LLovet, Laura; Carrión, José; Londoño, María; Lens, Sabela; Mariño, Zoe; Bartres, Concepció; Miquel, Rosa; Navasa, Miquel; Forns, Xavier
Summary: Little is known about the long‐term outcomes of mild hepatitis C recurrence after liver transplantation (LT). In an era where most patients request treatment with direct acting antivirals (DAAs), data on the natural history in these patients are relevant. We have prospectively assessed the clinical outcomes of 173 patients with mild hepatitis C recurrence 1 year after LT. The endpoints were cirrhosis development ( F = 4, HVPG ≥10 mmHg, liver stiffness measurement ≥14 kPa) and HCV‐related graft loss. After a median follow‐up of 80 months, the cumulative probability (CP) of HCV‐related graft loss 5 and 10 years after LT were only 3% and 10%, respectively. Graft cirrhosis developed in 26 (15%) patients over time, with a CP of 13% and 30% at 5 and 10 years after LT, respectively. The CP of cirrhosis 5 years after LT was only 8% in patients with a donor <50 years and AST <60 IU/l 1 year after LT ( n = 67), compared with 46% in those 24 individuals with both risk factors. Our data support an excellent long‐term outcome of patients with mild hepatitis C recurrence 1 year after LT. There are, however, some patients progressing to cirrhosis who can be easily identified and who should receive prompt antiviral therapy.